Analysis of articles in the Journal of Archives of Academic Emergency Medicine in 2022 - Saghaei Dehkordi, Somayeh; Yazdanbakhsh, Mehrnoosh (Archives of Academic Emergency Medicine, 2023)
In 2022, Archives of Academic Emergency Medicine (AAEM) has published 90 articles, all of which are indexed by SCOPUS, Web of Sciences, PubMed and some other databases. They have been authored by more than four hundred researchers from various countries, including but not limited to the United States, Japan, Korea, Canada, Ghana, France, Norway, India, China, Thailand, Malaysia, Pakistan, Greece, Viet Nam and Iran. In this editorial, we intend to provide an overview of the journal’s flow in 2022, like we did in 2021 (1), so that we can identify our strengths and weaknesses and provide a brief report on our performance to readers and authors, which they might find useful in becoming more familiar with the journal. This article could help the authors who are interested in publishing with us to become more familiar with the journal’s aim and scope, and also the editorial priorities and preferences.